P300 is upregulated by docetaxel and is a target in chemoresistant prostate cancer. Issue 3 (March 2020) - Gruber, Martina; Ferrone, Lavinia; Puhr, Martin; Santer, Frédéric R; Furlan, Tobias; Eder, Iris E; Sampson, Natalie; Schäfer, Georg; Handle, Florian; Culig, Zoran
Abstract : Administration of the microtubule inhibitor docetaxel is a common treatment for metastatic castration-resistant prostate cancer (mCRPC) and results in prolonged patient overall survival. Usually, after a short period of time chemotherapy resistance emerges and there is urgent need to find new therapeutic targets to overcome therapy resistance. The lysine-acetyltransferase p300 has been correlated to prostate cancer (PCa) progression. Here, we aimed to clarify a possible function of p300 in chemotherapy resistance and verify p300 as a target in chemoresistant PCa. Immunohistochemistry staining of tissue samples revealed significantly higher p300 protein expression in patients who received docetaxel as a neoadjuvant therapy compared to control patients. Elevated p300 expression was confirmed by analysis of publicly available patient data, where significantly higher p300 mRNA expression was found in tissue of mCRPC tumors of docetaxel-treated patients. Consistently, docetaxel-resistant PCa cells showed increased p300 protein expression compared to docetaxel-sensitive counterparts. Docetaxel treatment of PCa cells for 72 h resulted in elevated p300 expression. shRNA-mediated p300 knockdown did not alter colony formation efficiency in docetaxel-sensitive cells, but significantly reduced clonogenic potential of docetaxel-resistant cells. Downregulation of p300 in docetaxel-resistant cells also impaired cell migration and invasion. Taken together, we showed that p300 is upregulated by docetaxel, and our findings suggest that p300 is a possible co-target in treatment of chemoresistant PCa.